Contesting and Resisting Environmental Gentrification: Responses to New Paradoxes and Challenges for Urban Environmental Justice. (August 2016) - Pearsall, Hamil; Anguelovski, Isabelle
This paper analyzes environmental gentrification (EG), or the exclusion, marginalization, and displacement of long-term residents associated with sustainability planning or green developments and amenities, such as smart growth, public park renovations, and healthy food stores. We consider how activists, communities, and urban planners address these unjust processes and outcomes associated with EG and how these strategies compare to those used by environmental justice (EJ) activists. Our evaluation of relevant literature indicates several similarities with EJ resistance tactics, including collective neighborhood action, community organizing, and direct tactics. We also identify several different strategies enabled by certain urban environmental conditions, such as leveraging environmental policies and taking an active role in neighborhood redevelopment planning processes, collaborating with 'gentrifiers, ' and creating complementary policies to manage displacement and exclusion. Our analysis indicates a need for more research on how activists can better assert the social and political dimensions of sustainability and their right to the city, and how green and sustainable cities can achieve justice and equity.